Correlated and in-situ electrical transmission electron microscopy studies and related membrane-chip fabrication. (2nd September 2020) - Spies, Maria; Sadre Momtaz, Zahra; Lähnemann, Jonas; Anh Luong, Minh; Fernandez, Bruno; Fournier, Thierry; Monroy, Eva; I den Hertog, Martien
Abstract: Understanding the interplay between the structure, composition and opto-electronic properties of semiconductor nano-objects requires combining transmission electron microscopy (TEM) based techniques with electrical and optical measurements on the very same specimen. Recent developments in TEM technologies allow not only the identification and in-situ electrical characterization of a particular object, but also the direct visualization of its modification in-situ by techniques such as Joule heating. Over the past years, we have carried out a number of studies in these fields that are reviewed in this contribution. In particular, we discuss here i) correlated studies where the same unique object is characterized electro-optically and by TEM, ii) in-situ Joule heating studies where a solid-state metal-semiconductor reaction is monitored in the TEM, and iii) in-situ biasing studies to better understand the electrical properties of contacted single nanowires. In addition, we provide detailed fabrication steps for the silicon nitride membrane-chips crucial to these correlated and in-situ measurements.